2013
DOI: 10.1088/1468-6996/14/1/014205
|View full text |Cite
|
Sign up to set email alerts
|

Fe–Al–Mn–C lightweight structural alloys: a review on the microstructures and mechanical properties

Abstract: Adding a large amount of light elements such as aluminum to steels is not a new concept recalling that several Fe–Al–Mn–C alloys were patented in 1950s for replacement of nickel or chromium in corrosion resistance steels. However, the so-called lightweight steels or low-density steels were revisited recently, which is driven by demands from the industry where steel has served as a major structural material. Strengthening without loss of ductility has been a triumph in steel research, but lowering the density o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
143
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(149 citation statements)
references
References 45 publications
(108 reference statements)
5
143
0
1
Order By: Relevance
“…yield strength-to-mass density ratio) [4,5,17e27]. These lowdensity steels, mainly based on an FeeAleMneC alloy system containing high contents of Mn (16e28 wt.%), Al (3e12 wt.%) and C (0.7e1.2 wt.%), consist of face-centered cubic (fcc) austenite matrix and body-centered cubic (bcc) ferrite matrix and finely dispersed nanometer-sized k-carbides of (Fe,Mn) 3 AlC type (the so-called TRIPLEX steel) [18,19]. Recently, Kim et al [27] showed a new variation: their Fee16Mne10Ale0.86Ce5Ni high specific strength steel (HSSS) has a hard FeAl-type (B2) intermetallic compound as the strengthening second phase, and the alloying of Ni catalyzes the precipitation of B2 particles in the fcc matrix.…”
Section: Introductionmentioning
confidence: 99%
“…yield strength-to-mass density ratio) [4,5,17e27]. These lowdensity steels, mainly based on an FeeAleMneC alloy system containing high contents of Mn (16e28 wt.%), Al (3e12 wt.%) and C (0.7e1.2 wt.%), consist of face-centered cubic (fcc) austenite matrix and body-centered cubic (bcc) ferrite matrix and finely dispersed nanometer-sized k-carbides of (Fe,Mn) 3 AlC type (the so-called TRIPLEX steel) [18,19]. Recently, Kim et al [27] showed a new variation: their Fee16Mne10Ale0.86Ce5Ni high specific strength steel (HSSS) has a hard FeAl-type (B2) intermetallic compound as the strengthening second phase, and the alloying of Ni catalyzes the precipitation of B2 particles in the fcc matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Concepts of Fe-Al-Mn-C-based lightweight steels are fairly simple, but primary metallurgical issues are complicated [7][8]. This is because the lightweight steels can have ferritic, austenitic, or even multiphase structure, depending on contents of primary alloying elements of C, Mn, or Al, which complicatedly changes deformation mechanisms as well [9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Lightweight steel is desirable in manufacturing of fuel-economy and emission-reduction transportation components [1]. The challenge in fabrication of high Al steel includes clogging in continuous casting and cracking in cold working.…”
Section: Introductionmentioning
confidence: 99%